Analysis of the Impact of Foreign Object Debris on the Air Side for Flight Safety and Security at General Ahmad Yani International Airport Semarang - Indra Setya Sejati; Faiz Albana (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Airport is an area on land or water with predetermined boundaries that functions as a location for aircraft to land and take off, for people to get on and off, for loading and unloading of cargo, a place for intra and intermodal transportation, and which is equipped with basic and other supporting facilities besides facilities for aviation safety and security. This research uses a qualitative method with a descriptive research type. Researchers obtained data for this study at General Ahmad Yani International Airport, Semarang. Collecting data from this study, namely interviews, observation, and documentation. The results of this study indicate that the impact of Foreign Object Debris on the air side greatly disrupts flight activities. So that Apron Movement Control officers coordinate with stakeholders in order to handle Foreign Object Debris so as not to interfere with flight activities and create aviation safety and security.